CLINICAL CHARACTERISTICS AND REGIONAL FEATURES OF STREPTOCOCCAL TONSILLOPHARYNGITIS AMONG CHILDREN IN SURXONDARYO REGION (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the clinical course of tonsillopharyngitis caused by Group A beta-hemolytic streptococcus among children within the unique climatic conditions of the Surxondaryo region. The study examines the acute onset of the disease, the degree of manifestation of local and systemic symptoms, and the regional epidemiological situation. The article highlights the challenges of differential diagnosis and the critical importance of timely antibiotic therapy in preventing complications such as rheumatic fever and glomerulonephritis. The findings serve as practical recommendations for pediatricians and otorhinolaryngologists in the region.